Analisis Turn Of Year Terhadap Return Saham Di Periode Pergantian Tahun Pada Perusahaan Yang Terdaftar Di Indeks IDX30 BEI - Carin Mareta; Agatha Septiana Sri Ratnasari; Candra Astra Terenggana; Eunike Stefani Mendrofa (ATRABIS Jurnal Administrasi Bisnis (e-Journal), 2026)
Seasonal anomalies in the capital market continue to show mixed empirical findings, making stock return patterns around the turn of the year an important topic for investigation. This study aims to analyze differences in stock actual returns around the year-end period among companies listed in the IDX30 Index during 2023–2025. A quantitative comparative approach was employed using weekly actual return data from 21 companies selected through purposive sampling. Data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, the Kruskal–Wallis test, and the Mann–Whitney U post hoc test. The results indicate significant differences in actual returns across the observed periods, suggesting seasonal variations in stock return patterns around the turn of the year. However, these findings should not be interpreted as direct confirmation of the Turn of the Year Effect. This study contributes empirical evidence to the literature on seasonal anomalies in the Indonesian capital market and provides a basis for further research using more comprehensive analytical approaches.